MiRNA‐362‐3p induces cell cycle arrest through targeting of E2F1, USF2 and PTPN1 and is associated with recurrence of colorectal cancer. Issue 1 (12th February 2013) - Christensen, Lise Lotte; Tobiasen, Heidi; Holm, Anja; Schepeler, Troels; Ostenfeld, Marie S; Thorsen, Kasper; Rasmussen, Mads H.; Birkenkamp‐Demtroeder, Karin; Sieber, Oliver M.; Gibbs, Peter; Lubinski, Jan; Lamy, Philippe; et al.
<x xml:space="preserve">Abstract</x> Colorectal cancer (CRC) is one of the leading causes of cancer deaths in Western countries. A significant number of CRC patients undergoing curatively intended surgery subsequently develop recurrence and die from the disease. MicroRNAs (miRNAs) are aberrantly expressed in cancers and appear to have both diagnostic and prognostic significance. In this study, we identified novel miRNAs associated with recurrence of CRC, and their possible mechanism of action. TaqMan® Human MicroRNA Array Set v2.0 was used to profile the expression of 667 miRNAs in 14 normal colon mucosas and 46 microsatellite stable CRC tumors. Four miRNAs (miR‐362‐3p, miR‐570, miR‐148 a* and miR‐944) were expressed at a higher level in tumors from patients with no recurrence (p<0.015), compared with tumors from patients with recurrence. A significant association with increased disease free survival was confirmed for miR‐362‐3p in a second independent cohort of 43 CRC patients, using single TaqMan® microRNA assays. In vitro functional analysis showed that over‐expression of miR‐362‐3p in colon cancer cell lines reduced cell viability, and proliferation mainly due to cell cycle arrest. E2F1, USF2 and PTPN1 were identified as potential miR‐362‐3p targets by mRNA profiling of HCT116 cells over‐expressing miR‐362‐3p. Subsequently, these genes were confirmed as direct targets by Luciferase reporter assays and their knockdown in vitro phenocopied the effects of miR‐362‐3p over‐expression. We conclude that miR‐362‐3p may be a novel prognostic marker in CRC, and hypothesize that the positive effects of augmented miR‐362‐3p expression may in part be mediated through the targets E2F1, USF2 and PTPN1.